Computational Study and Analysis of the Optical Fiber Tip Mechanical Damage Threats during Laser Surgical Operations - Dawood, Munqith S. (Nahrain University College of Engineering Journal, 2014)
The damage of optical fiber tips during medical surgical applications of lasers in a liquid environment were noticed in arthroscopic and lithotripsy operations. The phenomenon of the laser produced cavitation bubbles and their collateral mechanical effects on the delivery fiber tip during these operations are studied. It was found that the optical fiber tip is subjected to the threats of the bubbles collapse transient pressures and to the strikes of the produced hammering jets beside the shearing forces due to the high speed bubbles flow. These frequently repeated mechanical forces are calculated for three different sizes of optical fibers. The results showed that to minimize the damage effects of these forces, it is preferable to use the smaller diameter of 200 ?m fiber, beside holding the fiber tip at about 5-7 mm away from the treated tissue or calculi targets during the operation to prolong its operating life and in the same time maintaining the efficient ablation